Changing the wind para meters on the Ukrainian territory during global climate changes - Laylko, V.I.; Elistratova, L.A.; Apostolov, A.A.; Khodorovskyi А.Ya. (Reports of the National Academy of Sciences of Ukraine, 2019)
Under the current conditions of climate change, the scientific interest in studying the trends of the future wind regime formation and its extreme manifestations, as well as the use of wind energy opportunities instead of traditional and already exhaustive ones, makes a priority research of the future wind conditions. The aim of this study is the analyzing and the evaluating of the wind parameter changes on the Ukrainian territory during the 1945-2015 period. The climatic processing of the wind parameters data is done with the methods of mathematical statistics. The data from 34 meteorological stations of Ukraine are used as the source materials of research. For each station and the whole Ukrainian territory, we computed: minimum, mean, maximum, standard deviation for each month, seasons, warm and cold periods, annual meanings. The wind speeds are calculated for 1945-2015; wind recurrence directions are determined for 1976-2015. In order to determine the dependence of the North Atlantic oscillation (NAO) on the wind regime in Ukraine, the monthly data of the NAO index for the 1945-2012 period are used as the initial data for identifying the reasons for changing the wind regime. The obtained results show a considerable deviation of the wind speed from 1975 to 1993 in the XX century and the sharp decline from 1994 to 2015, which shows the inertia of current atmospheric processes during this period. Joint analysis of the dynamics of NAO and the mean of wind speeds for cold period is carried out. It is found that the decrease of the mean wind speed on the Ukrainian territory correlates with the growth of the North Atlantic oscillation index intensity. The frequency of the wind repetition is analyzed in 16 directions for 40 years (1976-2015) for the Ukrainian territory. The meridian transference in tensification was maintained, but the sub-latitudinal wind mass movement was preserved. The analysis of mean and maximum speeds and directions of the wind shows the reduction of wind speeds over the Ukrainian territory in last 70 years. Any conclusions about the connections between wind speeds and directions have not been revealed yet.